Attributional Style as a Defense Mechanism of Student Activists’ Behavior - Bokhonkova , Yuliia; Serbin , Iyuriy; Zavatskа Nataliia; Danko , Dana (Insight: the psychological dimensions of society, 2025)
The aim of this study is to investigate the psychological patterns of the functioning of the attributional style as a defense mechanism of student activists’ behavior within the framework of their educational and professional activities. The participants in the study were student activists enrolled in socionomic educational programs in higher education institutions in Ukraine (n = 52). The respondents were between 18 and 25 years. Descriptive statistics of the sample: M = 20.21; Me = 20.00; Mo = 19.00; SD = ±4.19. Methods. Student activists were selected using the “Sociometry” methodology (Moreno, 1951). The research variables were assessed with psychodiagnostic tools: the “Attributional Style Questionnaire for Adults” (ASQ) (Peterson et al., 1982) and the “Ways of Coping Questionnaire” (Folkman & Lazarus, 1980). Non-parametric statistical criteria were used for the empirical data processing. Results. A descriptive research strategy was applied. High identical parameters for “personalization of the good” and “personalization of the bad” were recorded, indicating ambivalent characteristics of the attributional style. Ambivalence was explained through the characteristics of adolescence, particularly maximalist manifestations, extremes in achieving desired outcomes, and the convergent position of the respondents. It was found that the defense mechanisms of activist students’ behavior are realized exclusively through three constructive behavioral strategies – self-control, acceptance of responsibility, and problem-solving – and four destructive strategies – confrontation, distancing, escape, and seeking social support. The lack of a significant correlation with constructive reinterpretation was argued, suggesting that in the process and outcome of their educational and professional activities, respondents continuously engage in evaluation, reflection, rationalization, and intellectualization, which prevents them from perceiving constructive reinterpretation as a coping behavior. It was clarified and statistically confirmed that “personalization of the good” is favored in conjunction with the coping strategy of “acceptance of responsibility”. In contrast, “personalization of the bad” is favored in connection with the coping strategy “escape”. Discussion and Conclusions. It was summarized that the study of the attributional style as a defense mechanism of student activists’ behavior represented an established way to explain the causes and consequences of unfavorable events in the context of seeking constructive and destructive coping behaviors. The results obtained clarify a range of behavioral scenarios of student activists and may be of interest to those who organize work with student youth.